Occurrence and Health Effects of Hexabromocyclododecane: An Updated Review - Maria Lopes Marques; Elisa Cairrao (Toxics, 2023)
Hexabromocyclododecane (HBCD) is a non-aromatic compound belonging to the bromine flame retardant family and is a known persistent organic pollutant (POP). This compound accumulates easily in the environment and has a high half-life in water. With a variety of uses, the HBCD is found in house dust, electronics, insulation, and construction. There are several isomers and the most studied are α-, β-, and γ-HBCD. Initially used as a substitute for other flame retardants, the polybrominated diphenyl ethers (PBDEs), the discovery of its role as a POP made HBCD use and manufacturing restricted in Europe and other countries. The adverse effects on the environment and human health have been piling, either as a result from its accumulation or considering its power as an endocrine disruptor (ED). Furthermore, it has also been proven that it has detrimental effects on the neuronal system, endocrine system, cardiovascular system, liver, and the reproductive system. HBCD has also been linked to cytokine production, DNA damage, increased cell apoptosis, increased oxidative stress, and reactive oxygen species (ROS) production. Therefore, this review aims to compile the most recent studies regarding the negative effects of this compound on the environment and human health, describing the possible mechanisms by which this compound acts and its possible toxic effects.